Seasonal variation in cervical artery dissection in the Hunter New England region, New South Wales, Australia: A retrospective cohort study. (February 2017) - Thomas, Lucy C.; Makaroff, Andrew P.; Oldmeadow, Chris; Attia, John R.; Levi, Christopher R.
Abstract: Background: Cervical artery dissection (CAD) is a leading cause of ischemic stroke among middle aged adults, yet the aetiology remains poorly understood. There are reports from colder northern hemisphere sites of a seasonal pattern in the incidence of CAD. Seasonality may suggest some transient putative pro-inflammatory mechanism but it is unknown whether this also exists in temperate climates. Aims: To investigate the seasonal variation in incidence of CAD in the xx Region, Australia, and to compare seasonal incidence and selected clinical features between cases of carotid and vertebral artery dissection. Methods: This retrospective observational study investigated seasonal variation in CAD from a regional stroke register between 2006 and 2014. Clinical features and site of dissection were dichotomized into autumn-winter and spring-summer groups and compared with Chi 2 analysis. Results: 61 CAD events were identified. A strong trend was identified for CAD to occur more frequently in autumn-winter compared to spring-summer (38, 62.30% vs. 23, 37.70%; p = 0.054). Males were significantly more likely to present with vertebral artery dissection (VAD) than females (27, 73.0% vs 10, 41.7%; p = 0.014). A history of mild trauma was more common in VAD than internal carotid artery dissection (ICAD) (14, 41.2% vs 3, 13.0%; p = 0.023). Cases of VAD were more likely to have had an elevated white cell count than ICAD (16, 47.1% vs 5, 20.8%; p = 0.041). Conclusions: The findings suggest seasonal variation in the CAD incidence in a temperate region of Australia. Clinicians should be vigilant for CAD or risk of CAD during the colder months. Highlights: CAD may occur more commonly in the colder months -autumn/winter. Exposure to recent trauma was more common in cases of VAD in autumn/winter. Be caution with manual techniques in autumn/winter following recent infection. Be vigilant for potential of CAD in autumn/winter particularly following recent infection.